Hidden treasures: Marca Perú (PeruTM) and the recoding of neoliberal indigeneity in the Andes. Issue 3 (2nd July 2020) - Hirsch, Eric
ABSTRACT: Since 2011, the Peruvian national branding scheme – Marca Perú, or 'Peru TM ' – has oriented development projects that cultivate a thriving entrepreneurship rooted in ethnoracial difference throughout the country. In Andean Peru's Colca Valley, project staff announce these interventions in dramatic public events where rural villagers are revealed as newly minted indigenous entrepreneurs. This article offers a close reading of three tableaus in which neoliberal development projects display their success at cultivating inclusive indigenous entrepreneurship: a visit from Peru's tourism minister; an indigenous business pitch competition; and a microfinance bank's traditionally adorned parade float. Through public dramas in which rural villagers are exposed as newly neoliberal ethnoracial subjects, I argue, development projects discursively enact their investments as successful, while facilitating the state's abandonment of the region as a salutary hand-off of responsibility. However, villagers required to perform in these dramas resisted that departure; I argue that their resistance sought to entangle neoliberal programs in decidedly non-neoliberal obligations. Villagers worked to resist state 'forgetting' by engaging a variation on James Scott's 'hidden transcripts' that I call 'hidden enactments, ' or subtle tactical moves including the use of traditional adornments, abundant gift-giving, and overly enthusiastic participation that obligated development project staff to reciprocate.